"Ours is a business civilization" : the University of Oklahoma Bass Business History Collection with annotated bibliography of fifty treasures - (:unkn) unknown (Norman, Oklahoma : University of Oklahoma, 2018)
Imagine having the opportunity to explore oversize seventeenth-century parchment edicts of kings, stacks of gold-plated coins, boxes of 1930s stock certificates, and modern ledger books; to review inestimable incunabula from before Gutenberg; and to flip through personal files of business tycoons, maps of railroads, and scores of historically significant photographs. That was the opportunity afforded Oxford University scholar Chris Nitschke when, in 2017, he visited the University of Oklahoma Bass Business History Collection to find the specific archival resources he needed.

“I first heard of the Bass Business History Collection when I researched archival collections for my dissertation,” said Nitschke. “I admit I was surprised at first to learn that Oklahoma University would hold the archives of J. & W. Seligman & Co., a private bank founded in the nineteenth century. Yet it [traveling to Oklahoma] gave me a chance to shake things up a little bit in terms of destinations on my East Coast–heavy research trip.”

Nitschke came to the University of Oklahoma specifically to research the material in the Seligman Archives, one of the most important segments of the Bass Collection. “The Seligman Archives had looked very useful the first time I had looked at the online finding aid, and getting here did not change things. A more detailed printed finding aid allowed me to locate some additional material I would have overlooked otherwise. The material I targeted all along—original letter books by the partners of Seligman’s international bank—proved incredibly valuable.”

After a few days of research in Bass, Nitschke found what he was looking for: “Fortunately they [the Seligman letter books] covered just about the time period I was interested in . . . the Harry Bass Collection is in excellent shape.”

The experience of this international researcher is not unique to students and other researchers: the Bass Business Collection is a hidden gem of immense value.
Keywords: Bass Business History Collection (University of Oklahoma Libraries); Bass Business History Collection (University of Oklahoma Libraries) -- Catalogs; University of Oklahoma. Libraries -- Catalogs; Libraries -- Special collections -- Commerce; Commerce -- History -- Bibliography -- Catalogs